Perancangan Online Markeplace Untuk Developer Perumahan Di Kota Bengkulu - Asnawati, Asnawati; Khairil, Khairil; Zulfiandry, Ricky (UNIVED Press, 2020)
Residential property business, an activity in which someone invests in one or more houses, the implementation of which does not involve production costs. Because it does not use its own production costs, of course it is very safe for business people to control it, and the results can be taken at any time in the future in the form of profits. Currently, housing business players generally still market products manually, namely face to face (coming directly to the marketing location) to provide information to consumers about the housing sold by the developer. The online market application for housing developers in Bengkulu City is a medium that can be used by developers to market the housing they manage, and also to provide information to the public about housing in Bengkulu City. The domain of this online market application can be accessed via www.olmarketplacedevperumahan.online. In this online market there are 3 access rights for applications, namely administrator (can be placed in housing and data developers in Bengkulu City), developer (can update developer data and housing data applications), and community (can see developer information, housing, as well as installment simulations). In order for developers to access this online market application, developers must enter themselves into APERSI directly by entering the developer's profile. Then APERSI will provide a username and password to the developer, so that the developer can access this online marketplace application